Identification of subsurface fault using schlumberger configuration geoelectricity method. Case study in Opak River Yogyakarta - Ismi Lutfinur; Khumaedi K; Hadi Susanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
The Opak river is formed by fault. The earthquake in Yogyakarta on May 27th, 2006 had activated the Opak’s fault and caused secondary fault. The fault had made destruction of the infrastructure. This research aimed to determine the description of subsurface structure and to identify the location of the underground fault. The Schlumberger configuration of geoelectrical method was used for identifying the fault in the research area. The data collected in three lines of each which the length is 75 meters. The datas were processed by Res2dinv and Surfer 10.0. Based on the result of the process, the resistivity value are 5-1077 Ωm and the discontinue plane of the contour profile resistivity at depth function. The discontinuities of resistivity value can be interpreted the fault plane. The position of the fault in line A is 38 m, while on the line B and C, the fault locations are located at 33 m from the start point of the measurement. The faults in lines A, B, and C are straight with the strike N 113° E.